Tate Modern the handbook - Morris, Frances; Craig-Martin, Michael 1941-; Marr, Andrew; Wagstaff, Sheena; Serota, Nicholas (Tate Pub., 2006)
"This new, completely revised and updated edition of the best-selling Tate Modern Handbook introduces the reader to the building's stunning architecture, and to the unique organisation of the museum's collection of modern art. Writer and broadcaster Andrew Marr contributes an illuminating essay examining the Tate Modern phenomenon. Tate curator Frances Morris and Sheena Wagstaff write on Tate Modern's collection displays and on highlights from Tate Modern's programme since the year 2000 (including the stunning Turbine Hall commissions). Artist Michael Craig-Martin describes the process of transforming the vast industrial building into an art gallery." -- Provided by publisher